Unusual Presentation of Phacolytic Glaucoma: Simulating Microbial Keratitis - Srikant Kumar Sahu; Siddharth Keswarwani; Ruchi Mittal (Case Reports in Ophthalmological Medicine)
The differential diagnoses for phacolytic glaucoma are acute angle closure glaucoma, open angle glaucoma with uveitis, neovascular glaucoma, and glaucoma secondary to trauma. We report an unusual case where the dislocated cataractous lens firmly adherent to the corneal endothelium evoked a cellular reaction similar to phacolytic glaucoma but clinically appeared like a deep corneal abscess. The 73-year-old lady presented with severe photophobia, pain, and redness in the left eye for two months despite being on antibiotics and antifungals. Anterior chamber wash revealed a cataractous lens buried within the infiltrate, which was removed and sent for histopathological examination. Postoperatively she was treated with topical ofloxacin, homatropine, dorzolamide, timolol, and tapering dose of steroids. Histological confirmation of inflammation, histiocytic response, and giant cells around the lens material confirmed the ongoing phacolytic process. Photophobia, pain, and redness subsided following removal of the lens and surrounding cellular reaction. At her last visit, four months after surgery, she was comfortable.